2016
DOI: 10.1016/j.bbi.2016.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Self-rated health and interleukin-6: Longitudinal relationships in older adults

Abstract: Background Both self-rated health (SRH) and inflammation are implicated in chronic diseases and premature mortality. Better SRH is associated with lower proinflammatory cytokines, but there is little evidence about whether this relationship is more stable or dynamic. Objective To study the between- and within-person associations between SRH and IL-6. Methods Older adults (N = 131; Mage = 75 years) rated their health and provided blood samples for analysis of IL-6 at separate occasions every 6 months over a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…For example, we and others have reported significant correlations between IL‐6 and specific physical and psychological sickness symptoms, such as hyperalgesia, anorexia, cognitive impairments, or negative mood and feelings of social disconnection . Recently, an inverse relationship between IL‐6 and self‐rated health has been established in a large cohort of older adults . In medical conditions, IL‐6 has been proposed as a potential driver of sickness symptoms in cancer and cancer treatment‐related side effects .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…For example, we and others have reported significant correlations between IL‐6 and specific physical and psychological sickness symptoms, such as hyperalgesia, anorexia, cognitive impairments, or negative mood and feelings of social disconnection . Recently, an inverse relationship between IL‐6 and self‐rated health has been established in a large cohort of older adults . In medical conditions, IL‐6 has been proposed as a potential driver of sickness symptoms in cancer and cancer treatment‐related side effects .…”
Section: Discussionmentioning
confidence: 92%
“…16,17,20 Recently, an inverse relationship between IL-6 and self-rated health has been established in a large cohort of older adults. 21 In medical conditions, IL-6 has been proposed as a potential driver of sickness symptoms in cancer and cancer treatment-related side effects. 6,22 Our finding that IL-6 also predicted late sickness symptoms even though plasma concentrations had normalized during this time period can be explained by neural immune-to-brain pathways that seemed to trigger immediate but also delayed effects on central processes.…”
Section: Discussionmentioning
confidence: 99%
“…Also the relation between self-rated health and inflammation has mainly been investigated in cross-sectional studies. A recent longitudinal study demonstrated a stable relationship between poor self-rated health and higher IL-6 in older adults over several measurements 34 but this study did not include any measures of sickness behaviour. Because previous studies show that pro-inflammatory cytokines both causes sickness behaviour and poorer self-rated health, 35 , 36 the corresponding relationships should be investigated in allergic asthma.…”
Section: Discussionmentioning
confidence: 98%
“…Chronic levels of inflammation in turn have been linked to future health difficulties ranging from metabolic syndrome to cardiovascular disease (Dandona, Aljada, Chaudhuri, Mohanty, & Garg, 2005; Libby & Theroux, 2005). More specifically, high IL-6 levels have been associated with lower self-rated health among older adults (Arnberg, Lekander, Morey, & Segerstrom, 2016), and with specific disease processes related to premature aging, including tumor formation, arthritis, and osteoporosis (Hunter & Jones, 2015).…”
mentioning
confidence: 99%